Pembuatan Carboxymethyl Cellulose (CMC) Dari Batang Kelapa Sawit - Hariani, Razita; Fatmayati, Fatmayati (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
81.5 million m3 of palm oil stem is produced every year. Stem fiber can be used as source of cellulose for the making of carboxymethyl cellulose(CMC). CMC is widely used in the pharmaceutical, food, textile and cosmetic industries. The aim of this research is to determine the best reaction time. The procedure consists of 3 initial stages and 2 core stages, namely, sample preparation, reducing the size to 50 mesh, delignification using a 15% NaOH solution for 3 hours, bleaching using a 6% NaOCl solution for 3 hours, alkalization using isopropanol and alkalized with 15% NaOH for 1 hour, in the carboxymethylation stage, sodium monochloroacetate (NaMCA) was added with time variations of 2, 3, 4, 5 and 6 hours. The results showed that 5 hours reaction times produces CMC with degree of substitution of 1.64, a viscosity of 123.5 cP, a pH of 6.1 and a water content of 1.2%.